The diversity of immune reactions to balneotherapy and their accompaniments - Zoryana Struk; Oksana Mel'nyk; Walery Zukow; Igor Popovych (Kazimierz Wielki University, 2019)
Background.Earlier have been shown that the immune responses to course of drinking of Naftussya bioactive water from Truskavet's spa are ambiguous and individual. However, at Truskavets' spa water monotherapy is a rare exception for specific contingents, whereas the vast majority of patients use a balneotherapy complex: drinking of Naftussya, application of ozokerite and mineral baths. The immune responses to balneotherapeutic complex are also ambiguous which is a separate manifestation of the multivariate effects of balneological agents as well stressors on the body. Therefore, the purpose of this study is to analyze variants of immune responses to balneotherapeutic complex of Truskavets' spa. Material and methods. Theobjectofobservationwere 34menand 10 womenaged24-70yearsold,whocametotheTruskavets' spa for the treatment of chronic pyelonephritis combined withcholecystitis inremission. The survey was conducted twice, before and after balneotherapy (drinking Naftussya bioactive water three times a day, ozokerite applications, mineral baths every other day for 7-10 days). Immune status evaluated on a set of I and II levels recommended by the WHO. In portion of capillary blood we counted up Leukocytogram and calculated two variants of Adaptation Index as well as two variants of Strain Index by IL Popovych. We calculated also the Entropy of Immunocytogram and Leukocytogram. The condition of Microbiota is evaluated on the results of sowing of feces and urine. Results. Four variants of the immune responses to balneotherapeutic complex have been identified. In 40,9% of patients, initially normal immune status did not change significantly. In 31,8%, the lower boundary level of immunity is completely normalized. In 22,7% moderate immunosuppression is reduced, but not up to normal. However, in 4,5% of people, initially normal level of immunity are transformed into moderate immunosuppression. Discriminant analysis was conducted to identify exactly the parameters of the immunity and microbiota, in which the four immune response clusters differ significantly from each other.